The Epidemiology of Traumatic Brachial Plexus Injuries in England and Wales—A 32-Year Review - Abbey Boyle, MBChB, MSc; Chiraag Karia, MBChB, BSc; Ryckie G. Wade, MBBS, MClinEd, MSc, PhD; Fiona Lecky, MBChB, MSc, PhD; David Yates, MD, MA, MCh; Tom J Quick, MBBS, MA, MD; Grainne Bourke, MBBch, BAO (JBJS Open Access)
Background:. Traumatic brachial plexus injuries (TBPI) are often devastating and life-changing and are thought to be becoming more prevalent. Several studies have investigated the epidemiology of TBPI in other countries (e.g., United States, Brazil); however, a similar analysis is yet to be undertaken in England and Wales. The aim of this cohort study was to determine the incidence and epidemiology of TBPI in England and Wales. Methods:. The Trauma Audit and Research Network database was reviewed to identify 1,297 eligible patients admitted with TBPI between 1990 and 2022. Patient demographics, injury mechanism, associated injuries, and outcomes were analyzed. Results:. The median age of patients with TBPI was 41 years, and 77% (n = 997) were male. There was a significant difference in age between male patients and female patients, with male patients aged younger than 18 years (confidence interval 14.4-21.3) at the time of injury. The predominant injury mechanism was vehicle collision (65%), with 62% riding motorcycle or quad bikes. The majority of other injuries resulted from falls less than 2 m (19%). Falls less than 2 m were particularly prevalent in patients aged older than 65 years, who represented 19% of the cohort. TBPI was commonly associated with other injuries (94%), predominately bony injuries including dislocations and fractures. Conclusion:. This is the first epidemiological study of TBPI within England and Wales. Vehicle incidents, particularly involving motorcycles, are the commonest cause of TBPI; however, there is a substantial cohort of elderly patients sustaining TBPI, often from falls. These findings may aid improved and earlier recognition of TBPI, enabling timely management. Level of Evidence:. Level III. See Instructions for Authors for a complete description of levels of evidence.